Intraoperative open lung condition and postoperative pulmonary complications. A secondary analysis of iPROVE and iPROVE‐O2 trials. Issue 1 (22nd September 2021) - Ferrando, Carlos; Librero, Julian; Tusman, Gerardo; Serpa‐Neto, Ary; Villar, Jesús; Belda, Francisco J.; Costa, Eduardo; Amato, Marcelo B. P.; Suarez‐Sipmann, Fernando; ,
Abstract: Background: The preventive role of an intraoperative recruitment maneuver plus open lung approach (RM + OLA) ventilation on postoperative pulmonary complications (PPC) remains unclear. We aimed at investigating whether an intraoperative open lung condition reduces the risk of developing a composite of PPCs. Methods: Post hoc analysis of two randomized controlled trials including patients undergoing abdominal surgery. Patients were classified according to the intraoperative lung condition as "open" (OL) or "non‐open" (NOL) if PaO2 /FIO2 ratio was ≥ or <400 mmHg, respectively. We used a multivariable logistic regression model that included potential confounders selected with directed acyclic graphs (DAG) using Dagitty software built with variables that were considered clinically relevant based on biological mechanism or evidence from previously published data. PPCs included severe acute respiratory failure, acute respiratory distress syndrome, and pneumonia. Results: A total of 1480 patients were included in the final analysis, with 718 (49%) classified as OL. The rate of severe PPCs during the first seven postoperative days was 6.0% (7.9% in the NOL and 4.4% in the OL group, p = .007). OL was independently associated with a lower risk for severe PPCs during the first 7 and 30 postoperative days [odds ratio of 0.58 (95% CI 0.34–0.99, p = .04) and 0.56 (95% CI 0.34–0.94, p = .03), respectively]. Conclusions: An intraoperative open lung condition was associated with a reduced risk of developing severe PPCs in intermediate‐to‐high risk patients undergoing abdominal surgery. Trial registration: Registered at clinicaltrials.gov NCT02158923 (iPROVE), NCT02776046 (iPROVE‐O2).